Effect of Cinnamomum zeylanicum extract on scopolamine-induced cognitive impairment and oxidative stress in rats. (July 2015) - Jain, Seema; Sangma, Tultul; Shukla, Santosh Kumar; Mediratta, Pramod Kumari
<x content-type="archive" xml:space="preserve">Abstract</x> Objective Cinnamomum zeylanicum (CZ) is commonly known as cinnamon in traditional system of medicine having antibacterial, antioxidant, antidiabetic, hypolipidemic, and other activities. The present study was designed to assess the effect of extract of CZ bark on cognitive performance of scopolamine (SCOP)-treated rats and on associated altered oxidative stress markers in the brain of rats. Methods The extract was administered orally in three doses (100, 200, and 400 mg/kg) for a period of 21 days. SCOP was administered in the dose of 1.0 mg/kg intraperitoneally. The Morris water maze and passive avoidance step-down tasks were performed to assess cognitive functions. At the end of the study, oxidative stress parameters namely, malondialdehyde (MDA) and reduced glutathione (GSH) were also analyzed in the brain tissue of rats. Results SCOP-treated group showed significantly impaired acquisition and retention of memory as compared to the saline- and vehicle-treated groups. Pretreatment with CZ extract (200 and 400 mg/kg) for 21 days significantly reversed SCOP-induced amnesia as evidenced by increased step-down latency in passive avoidance and decreased latency in Morris water maze test compared to the SCOP-treated group. SCOP administration also caused the increase of MDA and reduction of GSH levels. Pretreatment with CZ extract (200 and 400 mg/kg) resulted in a significant decrease in MDA levels and increase in GSH levels as compared to the SCOP-treated animals. Discussion The results suggest that CZ can induce cognitive improvement in SCOP-treated rats and this effect can be attributed to a certain extent to decreased oxidative stress.